2018
DOI: 10.1002/er.4109
|View full text |Cite
|
Sign up to set email alerts
|

The indentation analysis triggering internal short circuit of lithium-ion pouch battery based on shape function theory

Abstract: Summary A novel indentation theory with homogenized, isotropic, and continuum model based on different shape functions is investigated to predict the mechanical behavior triggering internal short circuit of lithium‐ion pouch battery (LIPB) under indentation loading. By taking energy conservation principle into account, the relationship among indentation force, indentation displacement, and indentation region of LIPB is proposed. The results conclude that the effects of deformation region and indentation displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…The model can simulate the thermal field distribution under mechanical deformation and more comprehensively reflect the failure process of batteries. Hao et al studied the influence of different indenter sizes on the mechanical behaviors of batteries by combining theory with experiment. Xu et al tested batteries with different SOC and found that SOC had a significant effect on the mechanical properties of batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The model can simulate the thermal field distribution under mechanical deformation and more comprehensively reflect the failure process of batteries. Hao et al studied the influence of different indenter sizes on the mechanical behaviors of batteries by combining theory with experiment. Xu et al tested batteries with different SOC and found that SOC had a significant effect on the mechanical properties of batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The lithium dendrites may puncture the separator, which can trigger ISC or even explosion of the battery. According to previous researches, 19,25,[29][30][31][32] the exterior force increased gradually and then decreased with the increasing of indentation displacement, and ISC occurred together with mechanical failure, voltage dropping, and temperature rising. The above drastic changes meant that the failure of separators produced and direct contact occurred between positive and negative electrodes, which ultimately triggered ISC of LIPB under exterior loading ( Figure 1A).…”
Section: Introductionmentioning
confidence: 79%
“…According to the research by Hao et al, the total plastic energy of system is linear superposition of bending moment term and membrane force term. Because deformation shape of LIPB is similar to sinusoidal shape according to Figure C,D, so the sinusoidal shape function is proposed to describe the deformation field . Two independent variables, indentation displacement δ and deformation region λ , are used to analyze the resistance exterior force property of LIPB in this research.…”
Section: Indentation Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations